Epigenetic regulation of TNNT1 in gastrointestinal cancers prognostic implications and clinical significance - Jin Xie; Xin-Yang Qu; Rui-Min Wu; Jie Liu; Fan Cheng; Yu Zhang; Xu-Sheng Liu (Clinical Epigenetics, 2025)
Abstract Objectives This study aims to investigate the expression profile and clinical significance of the Troponin T Type 1 (TNNT1) gene across various digestive system tumors. By elucidating the role of TNNT1 in tumor progression, we hope to establish its potential as a prognostic biomarker and therapeutic target. Methods We assessed the expression levels of TNNT1 by employing bioinformatics analyses, including differential gene expression analysis and survival analysis utilizing data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. The impact of TNNT1 expression on patient prognosis was evaluated through Cox regression analyses. Furthermore, functional enrichment analysis was conducted to explore the biological pathways involved, alongside promoter methylation and mutation analyses, to elucidate its regulatory mechanisms. TNNT1 protein levels were analyzed through immunohistochemistry (IHC) on tissue microarray (TMA) sections. Results Our findings demonstrate that TNNT1 is significantly overexpressed in tumor tissues compared to normal tissues, with elevated expression levels correlating with poor prognosis specifically in colon adenocarcinoma (COAD), liver hepatocellular carcinoma and pancreatic adenocarcinoma. Functional analyses indicated that TNNT1 is involved in tumor aggressiveness-related processes such as epidermal development and keratinization. Notably, TNNT1 expression was linked to immune cell infiltration patterns, highlighting its potential role in modulating the tumor immune microenvironment. IHC analysis revealed significantly higher TNNT1 levels in COAD and rectum adenocarcinoma tissues compared to control samples. Conclusion This study underscores the potential of TNNT1 as a prognostic biomarker and therapeutic target in digestive system tumors. Our findings pave the way for future research aimed at elucidating the intricate mechanisms underlying TNNT1’s roles in tumor biology and its therapeutic implications in improving patient outcomes.